Mobile ions determine the luminescence yield of perovskite light-emitting diodes under pulsed operation - Kumawat, Naresh Kumar; Tress, Wolfgang; Gao, Feng (Nature communications, 2021)
The external quantum efficiency of perovskite light-emitting diodes (PeLEDs) has advanced quickly during the past few years. However, under pulsed operation, an operation mode which is important for display and visible light communication, the performance of PeLEDs changes a lot and requires in-depth understanding to facilitate these applications. Here, we report the response of PeLEDs under pulsed operation in the range of 10 Hz to 20 kHz. Beyond transient effects in the low frequencies, we find that for higher frequencies (>500 Hz) the transient electroluminescence intensity depends strongly on the duty cycle. This feature is much more pronounced and of different origin than that in conventional LEDs. We rationalise our experimental observations using a mathematical model and assign these features to the effect of mobile ionic charges in the perovskite. Our work also provides important implications for the operation of PeLEDs under the steady state, where accumulation of mobile ions at the interfaces could be beneficial for high electroluminescence yields but harmful for the long-term stability. Pulsed operation of perovskite light-emitting diodes is of particular importance in display and visible light communication, yet the ionic behaviour under this mode is not well-understood. Here, the authors reveal that the transient electroluminescence intensity increases with increasing pulse width as the result of accumulation of mobile ions at the interfaces.